Modified Direct Agglutination Test for Simplified Serologic Diagnosis of Leishmaniasis - Gómez-Ochoa, P. (American Society for Microbiology, 2003)
Human leishmaniasis is a severe health problem in many countries around the world. Hence, a cheap, reliable, and accurate diagnostic test is required to fight this disease. Perhaps the direct agglutination test (DAT) meets these criteria, but antigen elaboration involves many difficulties. We have developed a new antigen elaboration method, the EasyDAT method, that avoids the problems associated with the DAT. In this study, we compared the traditional DAT antigen method with our EasyDAT antigen method by using canine sera. The sensitivities (100%) and specificities (98.7%) were the same for both methods; we therefore concluded that the EasyDAT Leishmania antigen method simplifies serologic diagnosis, making this method easier and cheaper to use.